Economic and Social Survey of Asia and the Pacific 2023 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2023)
One of the main value additions of the Survey 2023 is a proposal for an augmented Debt Sustainability Analysis (DSA) approach that duly incorporates SDG investment needs, potential socioeconomic and environmental gains, government's structural policies that go beyond financial considerations, and government's resource mobilization strategies and financial capacity. The Survey 2023 also provides new insights on how to prevent potential public debt crises and resolve public debt distress in order to effectively pursue the SDGs. For example, in prevention of public debt crisis, governments will need to explore unconventional policy measures such as leveraging the potential of non-tax policy measures and public assets. In resolving public debt distress governments might need to bring the rising number of commercial debt creditors into discussions with the existing institutional investors, while fundamental policy actions to enhance fiscal resources are still needed, governments will also need to explore unconventional policy measures, such as leveraging the potential of non-tax policy measures and public assets amid rising public indebtedness. In resolving public debt distress, while the emergence of commercial creditors brings new opportunities as many of them are increasingly mindful about the importance of sustainable development, their participation in the existing global debt architecture is virtually missing. At the same time, several unconventional, SDG-aligned debt relief modalities have recently been proposed. Amid these and other changes in the global and Asia-Pacific debt landscapes and rising public indebtedness in the region, it is time to rethink public debt issues in support of the SDGs.